Case report: Two individuals with AEBP1-related classical-like EDS: Further clinical characterisation and description of novel AEBP1 variants - Angwin, Chloe; Ghali, Neeti; van Dijk, Fleur Stephanie (Frontiers in Genetics, 2023)
Introduction:AEBP1-related classical-like EDS (clEDS type 2) is a rare type of Ehlers–Danlos syndrome (EDS) that was first reported in 2016. There are overlapping clinical features with TNXB-related classical-like EDS (or clEDS type 1), including skin hyperextensibility, joint hypermobility, and easy bruising. There are currently nine reported individuals with AEBP1-related clEDS type 2. This report confirms previous findings and provides additional clinical and molecular data on this group of individuals. Materials and methods: Two individuals (P1 and P2), with features of a rare type of EDS, were clinically assessed in the London national EDS service and underwent genetic testing. Results: Genetic testing in P1 revealed likely pathogenic AEBP1 variants: c.821del:p. (Pro274Leufs*18) and c.2248T>C:p. (Trp750Arg). In P2 pathogenic AEBP1 variants, c.1012G>T:p. (Glu338*) and c.1930C>T:p. (Arg644*) were identified. Discussion: These two individuals increased the reported number of individuals with AEBP1-related clEDS to 11 (six females and five males). There are shared features with previously reported individuals, including hypermobility (11/11), skin hyperextensibility (11/11), presence of atrophic scarring (9/11), and easy bruising (10/11). In P1, a chronic right vertebral artery dissection, mild dilatation of the splenic artery, aberrant subclavian artery, and tortuous iliac arteries were observed at the age of 63 years. Cardiovascular disease has been reported, including mitral valve prolapse (4/11), peripheral arterial disease (1/11), and aortic root aneurysm requiring surgical intervention (1/11). Hair loss has been reported in 6/11 individuals (five females and one male), only one of which was documented to have a formal diagnosis of androgenetic alopecia, while other individuals were described as having thinning of hair, male pattern hair loss, or unspecified alopecia. Conclusion: The clinical features of individuals with AEBP1-related EDS have not been fully elucidated yet. Hair loss is present in 6/11 individuals with AEBP1-related clEDS and appears to be a feature of this condition. This is the first time hair loss has been formally reported as a characteristic feature in a rare type of EDS. Cardiovascular surveillance seems warranted in this condition because 2/11 individuals have evidence of arterial aneurysm and/or dissection. Further descriptions of affected individuals are necessary to update diagnostic criteria and management guidelines.